Cranial osteology of Geotrygon montana (Linnaeus, 1758) (Columbiformes: Columbidae) compared to other New World Columbiformes - Marceliano, Maria Luiza Videira; Donatelli, Reginaldo José; Posso, Sérgio Roberto (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2007)
Studies on cranial osteology of Columbidae are not frequent in the literature. This is the first description of the jaw apparatus of G. montana and we had as objectives: to compare its jaw apparatus with other New World Columbidae and thus broaden our anatomical knowledge of the family, and to identify anatomical characters for a future cladistic analysis. We studied 35 specimens from six genera of New World Columbidae. The results showed many structural differences among G. montana and other species, mainly related to the development of some cranial structures, as well as structures particular to some taxa. This possibly indicates that cranial osteology in Columbidae represents a useful tool to systematic studies.